AMPKα phosphatase Ppm1E upregulation in human gastric cancer is required for cell proliferation - Chen, Min-Bin (Oncotarget, 2017)
Activation of AMP-activated protein kinase (AMPK) is a valuable anti-cancer strategy. In the current study, we tested expression and potential function of Ca(2+)/calmodulin-dependent protein kinase phosphatase (Ppm1E), an AMPKα phosphatase, in human gastric cancers. Ppm1E expression was elevated in human gastric cancer tissues (vs. normal tissues), which was correlated with AMPK (p-AMPKα, Thr-172) dephosphorylation and mTOR complex 1 (mTORC1) activation. Ppm1E upregulation, AMPK inhibition and mTORC1 activation were also observed in human gastric cancer cell lines (AGS, HGC-27, and SNU601). Intriguingly, Ppm1E knockdown by shRNA induced AMPK activation, mTORC1 inactivation, and proliferation inhibition in AGS cells. On the other hand, forced over-expression of Ppm1E induced further AMPK inhibition and mTORC1 activation to enhance AGS cell proliferation. Remarkably, microRNA-135b-5p (“miR-135b-5p”), an anti-Ppm1E microRNA, was downregulated in both human gastric cancer tissues and cells. Reversely, miR-135b-5p exogenous expression caused Ppm1E depletion, AMPK activation, and AGC cell proliferation inhibition. Together, Ppm1E upregulation in human gastric cancer is important for cell proliferation, possible via regulating AMPK-mTOR signaling.